Peran Pertimbangan Hakim dalam Kasus Kepemilikan Senjata Tajam Oleh Anak - Habibah, Meiliani Zahira; Sunardi; Hernanda, Trias (Legalita, 2025)
Abstrak The judge's decision in the case of possession of sharp weapons by children illustrates the application of the principle of justice in the Indonesian legal system. This study aims to explore more deeply the basis for judges' considerations in upholding the principle of justice in juvenile criminal justice, which focuses on rehabilitation efforts and the formation of social norms in society. This study uses a normative juridical method by analyzing legal documents, applicable regulations, and case studies of court decisions that are the object of discussion by describing them from the sources collected, both from laws and court decisions that will be studied, to then draw conclusions. The principle of the best interests of the child emphasizes that the restorative justice and diversion approaches must be prioritized to avoid the negative impact of the criminal justice process on child development. If there is no indication of the use of weapons for criminal acts, then processing the child criminally can be considered excessive and contrary to the principle of justice. The judge chose to impose a prison sentence in accordance with the provisions of the Law, and provide the child with the opportunity to continue their education, while still punishing the actions that have been committed in accordance with applicable regulations. Kata Kunci: Juvenile Justice; Principles of Justice; Sharp Weapon.